Multidimensional Functional Phenotyping Based on Photoreceptor-Directed Temporal Contrast Sensitivity Defects in Inherited Retinal Diseases - Huchzermeyer, Cord; Stingl, Katarina; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2025)
PURPOSE. To identify patterns of functional defects in perifoveal photoreceptor-directed temporal contrast sensitivities (tCSs) in patients with inherited retinal diseases. METHODS. We retrospectively studied patients with RP1L1-associated occult macular dystrophy (OMD), Stargardt disease (STGD), and RP. Photoreceptor-directed tCS directed at L-, M-, S-cones and rods at different temporal frequencies were measured using a four-primary LED-stimulator with an annular test field (2° inner diameter and 12° outer diameter). Mean defects (MDs) were calculated by subtracting sensitivities from age-correlated normal values and averaging defects in frequency ranges where single postreceptoral pathways mediate flicker detection. Each patient was characterized by 6 MD values (one value each for S-cones [SMD] rods [RMD]; two values each for L- [LMDlow/high] and M-cones [MMDlow/high], where low refers to 1–6 Hz and high to 8–20 Hz temporal frequency ranges). Groups of similar phenotypes were identified with (supervised) decision trees and (unsupervised) hierarchical classification trees (based on nearest neighbors) and compared with the clinical diagnoses. RESULTS. The pruned decision tree used RMD for separating RP/STGD from normal/OMD, LMDlow for separating OMD from normal, and SMD for discriminating between RP and STGD. The accuracy was 66%. The hierarchical tree (independent of clinical diagnosis) was cut to four clusters, resulting in one cluster containing mainly normal participants, one cluster with severe L- and M-cone defects caused by OMD or STGD, one cluster with severe rod defects (4/5 with RP) and a large cluster with intermediate rod and cone defects that was dominated by RP and STGD patients. CONCLUSIONS. LMDlow, SMD, and RMD were the most important parameters. Photoreceptor-directed tCSs allow sophisticated functional phenotyping of inherited retinal diseases and complement other structural and functional parameters for genotype–phenotype correlations.
CRIS-Team Scopus Importer:2025-05-02
Keywords: occult macular dystrophy; retinitis pigmentosa; silent substitution; Stargardt’s disease; temporal contrast sensitivity